The role of nutritional risk evaluation in predicting adverse outcomes among patients with severe COVID-19 in Vietnam - Nguyen, Lan Huong Thi; Dang, Anh Kim; Tran, Tien Viet; Phan, Hai Thanh; Doan, Dao Anh Thi; Nguyen, Lien Bao Thi; Tran, Anh Minh; Do, Tung Dinh; Nguyen, Thang Ba; Nguyen, Tien Thanh; Nguyen, Binh Huy; Le, Huong Thi (Frontiers in Nutrition, 2023)
Introduction: As sufficient nutrition helps alleviate catabolic stress and modulate the systemic inflammatory response of the body, it plays an indispensable role in the good prognosis of critically ill patients. Thus, this study aimed to investigate the malnutrition of patients with severe COVID-19 and its association with adverse treatment outcomes. Methods: We conducted a retrospective cross-sectional study in two provincial hospitals in Hanoi from February to April 2022. Participants were patients with severe COVID-19 admitted to the Intensive Care Unit (ICU). Malnutrition risk were evaluated by Nutritional Risk Screening-2002 (NRS), Global Leadership Initiative on Malnutrition (GLIM), Prognostic Nutritional Index (PNI), and the adverse prognosis was assessed by Acute Physiology and Chronic Health Evaluation II (APACHE II). The multivariate receiver-operating characteristic (ROC) curve was applied to estimate the predictive ability of those criteria regarding worse treatment results. Results: The percentages of malnutrition measured by NRS, GLIM, PNI, and BMI were 62.6%, 51.5%, 42.9%, and 16.6%, respectively. Patients with more severe malnutrition assessed by GLIM, PNI, and having above target fasting blood glucose (FBG) (≥10.0 mmol/L) were more likely to have higher APACHE scores. PNI had a better diagnostic performance than NRS and BMI (AUC = 0.84, 0.81, and 0.82, respectively). In addition, FBG revealed a good prognostic implication (AUC = 0.84). Conclusion: A relatively high percentage of patients experienced moderate and severe malnutrition regardless of screening tools. Individuals at higher risk of malnutrition and high FBG were predicted to have more adverse treatment outcomes. It is recommended that nutritional screening should be conducted regularly, and personalizing nutritional care strategies is necessary to meet patients' nutrient demands and prevent other nutrition-related complications.